Pengaruh Tingkat Pendidikan dan Motivasi Terhadap Kesadaran Membayar Retribusi Parkir: (Studi Kasus pada Pasar Tingkat Maumere, Kab Sikka, Nusa Tenggara Timur) - Vincencio Sinar Da Gomez; Henrikus Herdi; Pipiet Niken Aurelia (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aimed to investigate the impact of education level and motivation on awareness of paying parking fees in the Pasar Tingkat Maumere parking area, Sikka Regency, East Nusa Tenggara.The research population comprised users of patking services,including both two-wheeled and four-wheeled vehicles,in the Pasar Tingkat Maumere parking area. The research employed a quantitative research approach, employing the survey method. The scope of the research included two independent variables (educational level and motivation) and one dependent variable (awareness of paying parking fees).The data sources consisted of both primary and secondary data.The data was collected by distributing 67 random sampling questionnaires.The data analysis technique used included descriptive statistics,multiple linear regression,data quality test, classical assumption test,and hypothesis test. The results of the research indicated that (1) Educational Level affected Awareness of Paying Parking Fees, (2)Motivation affected Awareness of Paying Parking Fees, and (3)both Education Level and Motivation had a simultaneous effect on Awareness of Paying Parking Fees.